A polymorphism in the bovine gamma-S-crystallin gene revealed by allele-specific amplification - Kemp, Stephen J.; Maillard, J.C.; Teale, A.J. (Wiley, 1993)
SummaryA polymorphism was detected in the 3′ untranslated region of the bovine gamma‐S‐crystallin gene by direct sequencing of polymerase chain reaction (PCR) products from genomic DNA of an N'Dama bull and a Boran cow. A set of three PCR primers was designed to detect this difference and thus give allele‐specific amplification. The two allele‐specific primers differ in length by 20 nucleotides so that the allelic products may be distinguished by simple agarose gel electrophoresis following a single PCR reaction. This provides a simple and rapid assay for this polymorphism.